Pentingnya Peran E-Commerce Dalam Mengembangkan Bisnis - Irzi Ahmad Fahrozi; Muhammad Irwan Padli Nasution (Journal Of Informatics And Busisnes, 2024)
Electronic-Commerce or e-commerce, also known as electronic commerce, is a method of buying and selling goods via Internet network services. E-commerce also includes e-business, and e-business has a very wide scope and not only includes transactions, but also collaboration with business partners, purchasing services, job opportunities, and others. Not only the www technology network, e-commerce also involves other non-computer technologies, for example data-based technology (data base), electronic mail (e-mail), and product and object delivery systems for e-commerce payments. And in business activities, the capabilities of e-commerce are still very large if you remember that the available target market is still wide open (especially in Indonesia).